2022
DOI: 10.3390/microorganisms10040799
|View full text |Cite
|
Sign up to set email alerts
|

Three Preceding Crops Increased the Yield of and Inhibited Clubroot Disease in Continuously Monocropped Chinese Cabbage by Regulating the Soil Properties and Rhizosphere Microbial Community

Abstract: Crop rotation can improve soil properties and is one of the important measures to prevent soil-borne diseases. This study aimed to evaluate the effects of different preceding crops on clubroot disease in Chinese cabbage and soil microorganisms, to provide a theoretical basis for the ecological control of clubroot scientifically. In this experiment, soybeans, potato onions, and wheat were used as the preceding crops and compared with the local preceding crop garlic. The growth of the Chinese cabbage, disease oc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
10
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 51 publications
0
10
0
Order By: Relevance
“…2 ). These fungal and bacterial phyla have been commonly detected in other studies on crop rotations 9 , 12 , 18 , 22 , 24 , 25 , 27 , 32 , 33 , 36 , 37 . We found different bacterial phylum compositions between two field soils, where the relative abundance of the Actinomycetota phylum in field_1 soils was clearly higher than that in field_2 soils (Fig.…”
Section: Discussionmentioning
confidence: 69%
See 2 more Smart Citations
“…2 ). These fungal and bacterial phyla have been commonly detected in other studies on crop rotations 9 , 12 , 18 , 22 , 24 , 25 , 27 , 32 , 33 , 36 , 37 . We found different bacterial phylum compositions between two field soils, where the relative abundance of the Actinomycetota phylum in field_1 soils was clearly higher than that in field_2 soils (Fig.…”
Section: Discussionmentioning
confidence: 69%
“…Regarding the communities in soils under crop rotation, many studies have indicated distinct β-diversities of soil bacteria and/or fungi between mono- and rotation-cropping 5 , 6 , 8 , 10 , 12 , 14 18 , 20 22 , 24 , 25 , 27 , 33 or among crop rotations with different crops and rotation sequences, places, and/or periods 5 , 10 , 11 , 15 , 18 22 , 24 , 25 , 32 , 33 ; however, the details of soil biota that change with plant growth have not been clarified in a crop-rotation cycle. We showed that the taxonomic variations indicated by β-diversities in the four sample groups were clearly distinguished by crops as well as by fields (Fig.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In contrast, the efficacy of 75% chlorothalonil and 50% carbendazim WP at three dilutions in the pot was lower than that in the field. The reasons for the difference in the efficacy of potted greenhouse control and field control could be owing to the presence of large numbers of microorganisms in the field soil ( Zhang Y. et al, 2022 ) and the existence of competitive microbial relationships; differences in soil properties, such as density, moisture, and organic matter; differences in environmental conditions for growth and development, such as weather and light hours, which are often more complex in the field than in the greenhouse.…”
Section: Discussionmentioning
confidence: 99%
“…For example, the biological control agent Streptomyces alfalfae XY25 T demonstrated promise in reducing clubroot disease, controlling rhizosphere bacterial and fungal populations in the rhizosphere of Chinese cabbage, and enhancing growth in greenhouse conditions (Hu et al, 2021 ); Trichoderma harzianum LTR-2 , which works by modifying the rhizosphere soil microbial population, is discovered to be an efficient biological control agent for cabbage clubroot (Li et al, 2020 ). Additionally, three preceding crops were shown to increase Chinese cabbage yield and suppress clubroot disease by regulating the soil environment and microbial communities in the rhizosphere (Zhang et al, 2022 ). Furthermore, three arsenic-tolerant bacterial strains were isolated from the Chinese cabbage rhizosphere and bulk soils, and these strains were capable of promoting the growth of edible tissues while reducing the uptake of arsenic and cadmium by these tissues (Wang et al, 2017 ).…”
Section: Introductionmentioning
confidence: 99%